If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4x + 3) = 5(3x + 4) Reorder the terms: 2(3 + 4x) = 5(3x + 4) (3 * 2 + 4x * 2) = 5(3x + 4) (6 + 8x) = 5(3x + 4) Reorder the terms: 6 + 8x = 5(4 + 3x) 6 + 8x = (4 * 5 + 3x * 5) 6 + 8x = (20 + 15x) Solving 6 + 8x = 20 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 6 + 8x + -15x = 20 + 15x + -15x Combine like terms: 8x + -15x = -7x 6 + -7x = 20 + 15x + -15x Combine like terms: 15x + -15x = 0 6 + -7x = 20 + 0 6 + -7x = 20 Add '-6' to each side of the equation. 6 + -6 + -7x = 20 + -6 Combine like terms: 6 + -6 = 0 0 + -7x = 20 + -6 -7x = 20 + -6 Combine like terms: 20 + -6 = 14 -7x = 14 Divide each side by '-7'. x = -2 Simplifying x = -2
| x(5x+21)+18=0 | | 5p-100=x | | 84-7x=11x+20 | | 2(5x+8)=3(4x-2) | | 2x+19=9x-44 | | 9+2.7t=4.8t-9 | | 8x-3y=-24 | | x-4+99=8 | | 4-7x=3x+1 | | 3x+47=7x+10 | | 12x-24-8x=-6x+16 | | 5x+13-4x=7+4x-6 | | 3x+14=85-8x | | 1/4=z+7/4 | | 14x+120+10x=360 | | 3[6x-4]=-52 | | 4+7(-12+x)=-38 | | 24+14x=x | | 3y+z=am | | [6x-4]=-52 | | 4x-10=6x+12 | | 14x+24=x | | 6x-4=-52 | | 6x-7=5x+6 | | 8x-1=8x-x | | 6x+8x=x | | -9=x+12 | | 3x+5x-15=37 | | 7x+1=7x-x | | a(b-c)=d | | x+108=100 | | 8+4d=36 |